The economic impact of political instability and mass civil protest - Samer Matta; Simon Appleton; Michael F. Bleaney (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2017)
Previous work has investigated whether political instability has a negative effect on economic growth, with mixed results, largely because political instability can take various forms. Using synthetic control methodology, which constructs a counterfactual in the absence of political instability, we estimate the output effect of 38 regime crises in the period 1970-2011. A crucial factor is whether crises are accompanied by mass civil protest. In the crises accompanied by mass civil protest, there is typically an immediate fall in output which is never recovered in the subsequent five years. In crises unaccompanied by protest, there are usually no significant effects.
Keywords: C23; F43; P16; 330; Aid; Political Instability; Economic Recovery; Synthetic Control Method